Comparison between VO2 max and serum lactate levels of male body builders and non-body builders in Pakistan - Saqib Javaid; Muniza Saeed; Hifza Noor lodhi (Journal of University Medical & Dental College, 2024)
ABSTRACTBACKGROUND AND OBJECTIVE: Volume oxygen maximum (VO2max) is a measure of physical fitness and athletic performance. Lactate accumulation during exercise occurs when anaerobic metabolism predominates. There is a difference of opinion among researchers on the intensity of exercise needed to cause this release and whether lactate levels play a role in it. The study aims to determine the effect of VO2max on the circulatory lactate levels and assess the comparison between the two parameters in male bodybuilders steroid non-users.METHODOLOGY: This study was conducted at the exercise physiology laboratory at the Postgraduate medical institute (PGMI) Lahore, Pakistan. The study involved 20 healthy male subjects within the age range of 20 to 35 years recruited through convenient non-probability sampling. Group I: non-bodybuilders, Group II: bodybuilders not using anabolic steroids. All participants underwent a graded exercise test on cardiopulmonary exercise testing (CPET) equipment up till exhaustion for VO2max assessment. Blood sampling was done pre and post-exercise (80% of VO2max) to measure blood lactate levels. Data was analyzed by SPSS version 23. Mean ± SD was calculated for quantitative variables. Paired t-test was used for comparison for pre- and post-exercise test variables. p-value <0.05 taken as statistically significant.RESULTS: Bodybuilders achieved a significantly higher VO2max as compared to non-bodybuilders (p <0.001). Blood lactate levels increased significantly in all the study groups at an exercise intensity of 80% of VO2max (p <0.001).CONCLUSION: Exercise intensity of 80% of VO2max is sufficient for the significant increase in blood lactate levels.